Sujeito aos grandão: reprodução social do campesinato na comunidade Cana Verde em Palestina de Goiás-GO - Galván, Gabriel Horacio (2020)
The present research aims to analyze the social reproduction strategies of peasant families in the Cana Verde community located in the municipality of Palestina de Goiás, in the southwest region of the state of Goiás. As for the approach, this is a qualitative research based on elements methodological features of ethnography. In the development of the research, 11 family production units were visited, in which 14 families are working, involving 46 people. The families that made up the survey are organized in the Associação dos Pequenos Produtores da Cana Verde (APROCAN). In order to achieve the proposed objective, secondary sources of information were used, such as digital repositories of theses, newspapers and scientific journals, in addition to databases from different sources. The primary results were produced using testimonials obtained during semi-structured and open interviews with community members between 32 and 80 years of age. Also, participant observation and the field notebook were used as complementary techniques. The results show that the strategies adopted by families, and which contribute to their social reproduction, can be analyzed based on material and symbolic elements. Analyzing the effects of the modernization of Brazilian agriculture, it was possible to identify changes in the Community's social and productive relations. However, families have responded by specializing productively, mainly in dairy farming, but still maintaining a diversified agriculture to meet the needs of the family group and, at the same time, making use of several marketing channels, short markets and establishing commercial relations with different agribusiness segments. From a symbolic point of view, the characteristics of the peasantry are reproduced through elements such as popular and religious festivals, music, food, work and social relations of compassion, neighborhood and solidarity. Regarding the effects caused by the economic logic of agribusiness and which hinder the social reproduction of families, the process of encroachment stands out, materialized in: applications of pesticides and the advance of the agricultural frontier to the limits of the Community; through monopoly rents; and through the control of genetic resources and the suppression of autonomous forms of fertilization. Due to the influence of agribusiness in the Community, it is possible to determine that its logic pressures families to deprive them of their means of production and life, at the same time that it also generates conditions for their reproduction, albeit contradictorily, through relationships with the “Canaverdian” families. Thus, in the light of the results, it was possible to consider the hypothesis established at the beginning of the research, when it started from the understanding that the social reproduction of the peasantry is due both to elements specific to the organization of the family and community unit, as well as to its relationship with the larger circuit (capitalist society). This is done through its insertion subordinated to the productive logic of agribusiness, with a visible recreation of the peasantry mediated by capital. Thus, through the results of the research, we defend the thesis of the permanence of the peasantry in capitalist society, related to the current of thought of the “end of the end of the peasantry”.